Personality: the human potential - Weiner, Melvin L. (Pergamon general psychology series, 1973)
Personality: The Human Potential is a collection of psychological studies that reflect some of the author's experiences in analyzing human conflict and suffering. Based on the spirit of psychotherapeutic work whose goal is to uncover the core of the patient's personality, the book explores the major emotional problems of contemporary life, particularly the critical turning-points in people's lives. Its purpose and challenge is to indicate how our underdeveloped and conflicted minds may be better understood and, through understanding, help us to realize our human potentialities. It demonstrates.